Penetapan Kadar Fenolik Total, Uji Aktivitas Tabir Surya Dan Antibakteri Propionibacterium acnes Dari Ekstrak Etanol Daun Gambir (Uncaria gambir Roxb) - Sumarsono, shoraya anis wulandari; Endang Sri Rejeki; Destik Wulandari (Akademi Farmasi Yarsi Pontianak, 2024)
Gambir leaves (Uncaria gambir Roxb) contain phenolic compounds that have the potential to act as sunscreen and have antibacterial activity. This study aims to determine the total phenolic content, SPF value of gambier leaf extract in vitro and antibacterial activity against Propionibacterium acnes. Gambier leaf extract was made using the maceration method with 96% ethanol solvent. Total phenolic content and sunscreen activity were tested by measuring absorption using UV-Vis spectrophotometry, while the antibacterial activity test used the agar well method. Data were analyzed using Microsoft Excel to test phenolic levels and SPF values, while for antibacterial activity using SPSS 25 with the One Way Anova test. The results showed that the total phenolic content of gambier leaf extract was 1.3322 mgGAE/g ± 0.2456 with ultra-protective SPF values at concentrations of 120, 100 and 80 ppm respectively, namely 31,94; 22,62; and 15,24. Gambir leaf extract has antibacterial activity against Propionibacterium acnes with inhibitory diameters at concentrations of 50, 25 and 12.5% respectively, namely 23,67; 18,00; and 14,57 mm.